Ancient Africa : A Global History, to 300 CE - Ehret, Christopher (Book collections on Project MUSE., 2023)
"A deep history of Africa, from 70,000 BCE to 300 CE, that synthesizes the archeological and historical linguistic evidence to tell an integrated global history of the continent. A framing chapter introduces the historical goals and issues of the book, recounting the terrible histories of recent centuries that led to Africa being wrongly treated as a peripheral other in the history of us all. Chapter two, "African Firsts in the History Technology," brings to light the histories of the independent inventions by Africans, living in different regions in the heart of the continent, of ceramic technology, more than 11,000 years ago; of the earliest cotton weaving technology in World History, 7,000-plus years ago; and of the earliest iron smelting, 4,000 or more years ago. Ehret then turns to agricultural innovations between the ninth and seventh millennia BCE, introducing the evidence that shows that Africa helped usher in the "Age of Agricultural Exchange," and was, on the whole, a net exporter of agricultural innovations into Eurasia (including twelve early essential crops, and domesticated donkeys). Chapter four, "Towns and Long-Distance Commerce in Ancient Africa," turns attention to the roles of Africans (particularly the regions of Sudan and the Congo Basin) in the development of new systems for trading over distance, which facilitated an emerging class of merchants, during the second and first millennia BCE. Next, "The Africanity of Ancient Egypt," summarizes the evidence of intensive cultural interaction between the lands several hundred kilometers south of the confluence of the White and Blue Niles in modern-day Sudan all the way north to Middle Egypt. Finally, a closing chapter, "Africa and Africans in Global History," takes up the problem of how to bring what we have learned about 'ancient' Africa integrally into how we tell World History and proposes a new periodization of African and World History over the ages from around 68,000 BCE-when true, fully modern humans all still lived in eastern Africa-down to the first three centuries CE"--